Building knowledge about language for teaching IELTS writing tasks: A genre-based approach - Ika Lestari Damayanti; Fuad Abdul Hamied; Harni Kartika-Ningsih; Nindya Soraya Dharma (Studies in English Language and Education, 2023)
As a widely used English proficiency test that includes a writing test component, IELTS raises pedagogical challenges that require high-stake literacy skills to meet the demands of the assessment criteria. Many studies on various teaching strategies for writing tasks in IELTS preparation courses have been conducted. However, more information about explicit instructions is needed to help test-taker candidates respond to the IELTS writing tasks effectively. This paper reports on a small-scale pilot project implementing a new generation of genre pedagogy, the Reading to Learn (R2L), for teaching IELTS writing to 14 government-sponsored student candidates at a public university language center in Indonesia. The project aimed first to identify the linguistic demands of IELTS writing, particularly Task 2. The identification of linguistic patterns was then used to design and implement the intervention. Second, it mapped the participants’ writing skills before and after the intervention. The data were drawn from IELTS teaching materials and the participants’ writing tasks before and after the intervention. Based on the genre analysis, the IELTS Writing Task 2 requires the test takers to respond to the tasks by taking one side or discussing two sides. Making such linguistic demands explicit to the participants in the writing class helped them respond to the tasks more successfully. As a result of their involvement in the intervention, the participants, including those with low English proficiency, demonstrated their ability to write more coherent texts. This study offered a genre-based teaching model for preparing EFL students intending to take English writing tests.